The cultural adaptation of the Friendship Bench Intervention to address perinatal psychological distress in Sierra Leone: an application of the ADAPT-ITT framework and the Ecological Validity Model - Bah, Abdulai Jawo; Wurie, Haja Ramatulai; Samai, Mohamed; Horn, Rebecca; Ager, Alastair (Frontiers in Psychiatry, 2025)
BackgroundIn Sierra Leone, women of reproductive age represent a significant portion of the population and face heightened mental health challenges due to the lasting effects of civil war, the Ebola epidemic, and the COVID-19 pandemic. This study aimed to culturally adapt the Friendship Bench Intervention (FBI) for perinatal psychological distress in Sierra Leone.MethodWe utilized the ADAPT-ITT framework and Bernal’s Ecological Validity Model (EVM) for culturally adapting the FBI’s process and content. The adaptation stages included a formative study to assess perinatal women’s mental health needs. We screened the FBI for modifications based on the data from the formative study and EVM. The initial FBI manual was presented to mother-mother support groups (MMSGs, n=5) and primary health workers (n=3) for feedback (version 1.0). A theatre test with perinatal women (n=10) was conducted led by MMSGs, yielding further feedback (version 2.0). The revised manual was then reviewed by topical experts (n=2), whose insights were incorporated (version 3.0).ResultsThe Friendship Bench manual for Sierra Leone has been revised to better meet the cultural needs of perinatal women. The cover now illustrates an elderly woman conversing with a new mother, emphasizing community support. Culturally relevant idioms, such as “poil at” and “mind not steady,” replace previous terms, and new screening tools, the Sierra Leone Perinatal Psychological Distress Scale (SLPPDS) and the Function Scale, have been introduced. The problem-solving therapy was simplified from seven to four steps, and training duration was reduced from nine days to two, using visual aids to enhance comprehension for those with low literacy levels.ConclusionThrough this systematic approach, we successfully culturally adapted the FBI for treating perinatal psychological distress in Sierra Leone. The next step is to evaluate it feasibility, acceptability, and preliminary effectiveness in perinatal care settings.